Var and Manəstən Adpositions in Gilaki Language - Elahe Hoseyni Matak; Ehsan Changizi (̒Ilm-i Zabān, 2020)
In Gilaki language, propositions like, "var / vir, virja, bija" are used to transfer the meaning "near, beside, with, by side of ...". These propositions, in addition to concept "place", also signify the concept of accompaniment. This paper is an attempt to investigate the core meaning of var, its semantic changes and the process of its grammaticalization using the data from Avestan and Middle Persian. Var's relationship with virja and bija is also discussed. Gilaki language’s data is provided by Rastorgueva et al. (2012) and some local poems. Var in Gilaki, is derived from varah in Avestan and war in Middle Persian (= chest). As the result of metonymic use of language, this word has got some meanings like "beside, with, by the side of …". By passing time, it has been used to point out the space around human, which is under his control. It is shown that this proposition is merged with the preposition ja / je and the result is the formation of the preposition virja. Since the core meaning of "var" signifies the human body and in categorical metaphor's model, human bodies associated with object-person category, these propositions also include the semantic feature of accompaniment. Moreover, the infinitive "manestan" (to resemble), have changed into proposition in the noun phrase constructions.